2014
DOI: 10.1159/000360000
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the Routine Use of a Nasopharyngeal Airway (Wendl Tube) during Endoscopic Propofol-Based Sedation

Abstract: Background/Aims: Insertion of a nasopharyngeal airway (NPA) during endoscopic sedation is only recommended in the event of respiratory problems. We evaluated the safety and efficacy of routine insertion of an NPA during sedation in gastrointestinal (GI) endoscopy. Methods: Between July 2009 and April 2012, patients with colonoscopy or expected longer-lasting or therapeutic upper GI endoscopy were pseudo-randomized in a weekly alternating fashion to perform sedation (midazolam in combination with propofol) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
1
10
0
1
Order By: Relevance
“…In addition, increasing the concentration of inspired oxygen and performing chin lift maneuvers and jaw thrusts are simple, effective strategies to prevent hypoxemia. Furthermore, routine use of the nasopharyngeal airway during general anesthesia in this subgroup of patients might reduce the frequency of hypoxemic events during endoscopic sedation 1 . Ultimately, Cohen suggested that an ideal short-acting sedative agent such as propofol, without adjunctive agents such as opioids or benzodiazepines, would be most appropriate for high-risk patients 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, increasing the concentration of inspired oxygen and performing chin lift maneuvers and jaw thrusts are simple, effective strategies to prevent hypoxemia. Furthermore, routine use of the nasopharyngeal airway during general anesthesia in this subgroup of patients might reduce the frequency of hypoxemic events during endoscopic sedation 1 . Ultimately, Cohen suggested that an ideal short-acting sedative agent such as propofol, without adjunctive agents such as opioids or benzodiazepines, would be most appropriate for high-risk patients 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Drug-induced sedation in endoscopic procedures improves patient comfort and facilitates endoscopic performance 1 . Propofol-mediated sedation has become increasingly popular during endoscopic procedures because of its rapid onset of action and short duration of effect 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the endoscopist, a well-trained sedation professional should be responsible for clinical and instrumental monitoring of the patient during GI endoscopy, as recommended at the International Sedation Endoscopy Workshop in 2009 [ 19 - 21 ]. In Europe in particular the debate on propofol-based sedation is strongly influenced by different legislation between countries and reimbursement matters and unfortunately not always by quality arguments [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be proven by the analysis of a prospective complication registry of 388,404 gastrointestinal endoscopic procedures in the typical NAAP manner [11,12]. In this context the study by Müller et al [13] should be seen.…”
mentioning
confidence: 99%